Poly(amide thioether)s by addition of ethanedithiol to diallylamides - Biçak, Niyazi; Karaoğlan, Sevim (Wiley, 1998)
The preparation of poly(amide thioether)s by addition of ethanedithiol to diallylamides in the presence or absence of peroxide catalysts is reported for the first time. Diallylamide monomers N,N'-diallyloxalamide, N,N'-diallylmalonamide and N,N'-diallylterephthalamide have been prepared by aminolysis of the corresponding esters with allylamine. The structures of the resulting polymers have been elucidated by elemental microanalysis and 1H NMR and IR spectroscopy. The polymers obtained both as Markovnikov and anti-Markovnikov types of addition are highly crystalline compounds. Poly(amid-thioether) wurden durch Addition von Ethandithiol an Diallylamide in Gegenwart oder Abwesenheit von Peroxidkatalysatoren erstmalig hergestellt. Die Diallylamid-Monomeren N,N'-Diallyloxalamid, N,N'-Diallylmalonamid und N,N'-Diallylterephthalamid wurden durch Aminolyse der entsprechenden Ester mit Allylamin synthetisiert. Die Strukturen der erhaltenen Polymere wurden mittels Mikroanalyse und 1H NMR- sowie IR-Spektroskopie ermittelt. Die Polymeren, die sowohl als Markovnikov- als auch anti-Markovnikov-Additionsprodukte gebildet werden, sind hochkristallin.